The Effect of Five Finger Relaxation on Mother's Anxiety Level Third Trimester Primigravida in Tuban Health Center Working Area - Nurus Safa'ah; Tiara Putri Ryandini; Dyah Pitaloka; Pidiya Ayu Lestari (Universitas Muhammadiyah Semarang, 2022)
Anxiety is an individual mental or psychological state that brings up feelings like worry, fear, anxiety, confusion, and others. One of the treatments for those problems is five-finger relaxation. This study aims to determine the effect of five-finger relaxation on the anxiety level of primigravida mothers during the third trimester at the Tuban Public Health Center’s working area. The methods used Pre-experimental (static-group comparison design) and a cross-sectional study approach were used as the study’s method. The sampling technique used a simple random sampling with 36 primigravida mothers as the sample. SOP and questionnaires sheets were used as the instruments. Paired sample T-test was used to analyze the data. The study results showed a decrease in anxiety levels in third-trimester primigravida mothers in the experimental group after being given five-finger relaxation therapy with 1 treatment during the study. Five-finger relaxation is effective in non-pharmacological treatment. So it can be concluded that there is a difference in the level of anxiety of third-trimester primigravida mothers in the experimental group and the control group